On convergence and solvability of an elliptic equation by finite difference method - RAMOS, Anderson de Jesus Araújo (Universidade Federal do Pará, 2018)
In this article we deal with questions of convergence, existence and uniqueness of the numerical solutions for a discretized elliptic problem by using finite difference method. In order to show existence and uniqueness of numerical solutions we will use a suitable variational setup (at discrete level) to guarantee the existence of a numerical solution by means of a finite difference method